O que cabe na pausa : o sensível no modo de fazer conhecimento das parteiras e parteiros indígenas da região das serras na terra indígena Raposa Serra do Sol - Maria Christina Almeida Barra (2020)
This paper aims to discuss the construction of a knowledge named as “traditional” and “indigenous” from the traditional indigenous midwife category as proposed by public health policies. Based on statements given by indigenous women and men, who call themselves midwives, in the meeting of midwives, praying men and shamans: “Revivendo nossa cultura e nossa sabedoria indígena”, held in Região das Serras, Raposa Serra do Sol, Indigenous Land, Brazil – this work seeks to consider how the indigenous way of making knowledge, which is sensible and imagetic, transforms itself and takes new shapes in relation to the ocidental medicine way of making knowledge embedded in traditional midwife training courses.